Can toxicities induced by antituberculosis drugs be better managed in diabetic patients?. Issue 1 (20th July 2017) - Yew, Wing Wai; Chan, Denise P.; Leung, Chi Chiu; Zhang, Ying; Wang, Ruibing; Ng, Phoebe; Lee, Simon M.
The converging epidemics of tuberculosis and diabetes mellitus worldwide have immense healthcare implications [1]. Diabetes mellitus adversely impacts tuberculosis treatment outcomes, largely as delayed bacteriological conversion and lower cure, as well as higher relapse and mortality. Worsened drug resistance scenarios may also result. In addition, diabetic patients experience a higher risk of toxicities induced by drugs used for treating drug-susceptible tuberculosis and multidrug-resistant tuberculosis (table 1) [1, 2]. Clearly, these adverse reactions merit better management. Elucidating mechanisms of antituberculosis-drug-induced toxicities in diabetic patients helps in clinical management http://ow.ly/92vA30cAlBW